Transgenerational metabolomic fingerprints in mice ancestrally exposed to the obesogen TBT. (December 2021) - Chamorro-García, Raquel; Poupin, Nathalie; Tremblay-Franco, Marie; Canlet, Cécile; Egusquiza, Riann; Gautier, Roselyne; Jouanin, Isabelle; Shoucri, Bassem M.; Blumberg, Bruce; Zalko, Daniel
Highlights: First application of metabolomics to unveil the transgenerational effects of Tributyltin. Ancestral (F0) exposure to Tributyltin drives deep metabolic changes in F3/F4 mice. Changes in male's plasmatic metabolome precede obesogenic effects caused by dietary fat. Ancestral tributyltin exposure impairs liver biotransformation capacities in females. Abstract: Background: Endocrine disrupting chemicals (EDCs) contribute to the etiology of metabolic disorders such as obesity, insulin resistance and hepatic dysfunction. Concern is growing about the consequences of perinatal EDC exposure on disease predisposition later in life. Metabolomics are promising approaches for studying long-term consequences of early life EDC exposure. These approaches allow for the identification and characterization of biomarkers of direct or ancestral exposures that could be diagnostic for individual susceptibility to disease and help to understand mechanisms through which EDCs act. Objectives: We sought to identify metabolomic fingerprints in mice ancestrally exposed to the model obesogen tributyltin (TBT), to assess whether metabolomics could discriminate potential trans-generational susceptibility to obesity and recognize metabolic pathways modulated by ancestral TBT exposure. Methods: We used non-targeted 1 H NMR metabolomic analyses of plasma and liver samples collected from male and female mice ancestrally exposed to TBT in two independent transgenerational experiments in which F3 and F4 males became obese when challenged with increased dietary fat. Results: Metabolomics confirmed transgenerational obesogenic effects of environmentally relevant doses of TBT in F3 and F4 males, in two independent studies. Although females never became obese, their specific metabolomic fingerprint evidenced distinct transgenerational effects of TBT in female mice consistent with impaired capacity for liver biotransformation. Discussion: This study is the first application of metabolomics to unveil the transgenerational effects of EDC exposure. Very early, significant changes in the plasma metabolome were observed in animals ancestrally exposed to TBT. These changes preceded the onset of obesogenic effects elicited by increased dietary fat in the TBT groups, and which ultimately resulted in significant changes in the liver metabolome. Development of metabolomic fingerprints could facilitate the identification of individuals carrying the signature of ancestral obesogen exposure that might increase their susceptibility to other risk factor such as increased dietary fat.